Reviving the Islamic economic system through shariah-based public policy - Mohd Yusop, Mohd Mahyudi (Emerald Group Publishing, 2015)
Abstract Purpose – The paper aims to revive the Islamic economic system discourse given the increasing interest in the moral economy agenda. Design/methodology/approach – Proponents of Islamic economics theorise that the Islamic system presents the ideal form of a socio-economic order. However, the reported huge gap between theoretical construct and real activities seems to support the critics’ claim that it is a mere utopian state that directly challenges the viability of the Islamic economy idea. Findings – The fact of the matter is that homo economicus is overpowering homo Islamicus despite the presupposed position of homo Islamicus as the mainstay of Islamic economics. Research limitations/implications – To manifest the Islamic economic system notion further, it is argued that a shariah-based values infusion policy (VIP) needs to be formulated to actualise the predominance of homo Islamicus. Practical implications – Owing to the overarching and holistic nature of the proposed public policy, the operations of individuals, firms and state agencies should have the tendency to reflect the expected behaviour of homo Islamicus better than the present state of affairs. Social implications – The success of the VIP would include the enhancement of social integration and cohesion. Originality/value – The link between moral economy, homo Islamicus and public policy is clearly established. Thus, this research guides policy makers in promoting the Islamic economic system as a universally-aspired moral economy project. Keywords Moral economy, Comparative economic systems, Homo economicus, Homo Islamicus, Islamic countries, Shariah-based public policy Paper type Conceptual paper